Extracellular Hydrolytic Enzymes Action of Alternaria Species under the Influence of Different Nutritional Sources - Ashok M.Chavan, Sulochana R. Rathod* and (Journal of Ecobiotechnology, 2010)
Influence of nutritional sources like carbohydrates, nitrogen, phosphorous and sulpher on amylase, lipase and protease action of six Alternaria species viz. A. alternata, A. citri, A. crassa ,A. macrospora, A. dianthicola and A. tenuissima were studied. It was reported that Carboxy methyl cellulose (CMC), ferrous sulphate, calcium sulphate, sodium sulphate, copper sulphate and sodium dihydrogen orthophosphate retarded the enzyme action of some Alternaria species.